Fra Lippo Lippi: Browning’s Reflections on Life and Art - Anis, Rehnuma Bint (IIUC Studies, 2009)
The state of intellectual curiosity in the twenty first century is that there is no publicly accepted moral and emotional Truth, there are only perspectives towards it - those partial meanings which individuals may get a glimpse of at particular moments but which, formulated as ideas for other moments and people, become problematical. The empiricism in Robert Browning's dramatic monologue, âFra Lippo Lippi', as demonstrated by its disequilibrium between sympathy and judgement, is a sign that it imitates not life but a particular perspective towards life, somebody's experience of it. Robert Browning gives us his own version of Truth, about life and art, as he saw it, in one of his most delightful and revealing monologures, âFra Lippo Lippi'. We find in Browning's poetry what our age most needs, faith which is adequate and consistent with our intellectual culture and which indicates the direction in which we must look for the religion of the future. This paper explores the purpose of life on this earth in the light of Browning's reflections on life and art in âFra Lippo Lippi'. Doi: IIUC Studies Vol.2 2004